Language Pedagogy and Non-transience in the Flipped Classroom - Una Cunningham (Flexible Learning Association of New Zealand, 2016)
High connectivity at tertiary institutions, and students who are often equipped with laptops and/or tablets as well as smartphones, have resulted in language learners being able to freely access technology and the internet. Reference tools such as dictionaries, concordancers, translators, and thesauri, with pronunciation and usage tips, are available at the touch of a screen. The web brings a virtually endless corpus of authentic written and spoken target language usage, and instant communication with target language speakers anywhere. Video recordings of teaching or materials created for language learners can be viewed and reviewed at the learner's convenience and reused by the teacher, freeing contact time for interaction. This paper distinguishes between asynchrony and non-transience and discusses which material can best be offered to language learners in tertiary education in a non-transient or enduring form rather than as live teaching, why this might be a good idea, and how to create and curate non-transient resources for individualised language learning.